LEGISLASI HUKUM KEWARISAN DI INDONESIA - Fauzi, Mohammad Yasir (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2016)
Inheritance law is one part of the civil law as a wholeand is the smallest part of family law. Inheritancelaw in Indonesia is still very pluralistic covers threeareas of law, namely the customary inheritance law,Islamic law and the civil law of inheritance (BW).The third system of inheritance law applies despitetogether but in reality do not always go hand inhand, and often lead to conflict. For people who areMuslims, Islamic inheritance law is based on IslamicLaw Compilation (KHI) is not a legal provision thatis imperative. Thus Islamic law for Muslims inIndonesia are voluntary (choice of law). How toshape legislation inheritance law in Indonesia, be atopic of studies in this paper.